Solution:
Consider the polynomial:

now, to find the roots of the above equation, use the following quadratic equation:
![x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/rxvf73usjbbwyik14knxdemoz21vfz2ufc.png)
in this case, we have that a = 8, b = 16 and c = 8. So, replacing the above data on the previous equation we get:
![x=\frac{-16\pm\sqrt[]{16^2^{}-4(8)(8)}}{2(8)}](https://img.qammunity.org/2023/formulas/mathematics/college/lifkpdq5l48v1pswz1jxe6u3dau0r96mmh.png)
this gives us :

thus, we can conclude that the root of the given polynomial is
